Metagenomic signatures of a tropical mining-impacted stream reveal complex microbial and metabolic networks. (October 2016) - Reis, Mariana P.; Dias, Marcela F.; Costa, Patrícia S.; Ávila, Marcelo P.; Leite, Laura R.; de Araújo, Flávio M.G.; Salim, Anna C.M.; Bucciarelli-Rodriguez, Mônica; Oliveira, Guilherme; Chartone-Souza, Edmar; Nascimento, Andréa M.A.
Abstract: Bacteria from aquatic ecosystems significantly contribute to biogeochemical cycles, but details of their community structure in tropical mining-impacted environments remain unexplored. In this study, we analyzed a bacterial community from circumneutral-pH tropical stream sediment by 16S rRNA and shotgun deep sequencing. Carrapatos stream sediment, which has been exposed to metal stress due to gold and iron mining (21 [g Fe]/kg), revealed a diverse community, with predominance of Proteobacteria (39.4%), Bacteroidetes (12.2%), and Parcubacteria (11.4%). Among Proteobacteria, the most abundant reads were assigned to neutrophilic iron-oxidizing taxa, such as Gallionella, Sideroxydans, and Mariprofundus, which are involved in Fe cycling and harbor several metal resistance genes. Functional analysis revealed a large number of genes participating in nitrogen and methane metabolic pathways despite the low concentrations of inorganic nitrogen in the Carrapatos stream. Our findings provide important insights into bacterial community interactions in a mining-impacted environment. Highlights: The microbiome of a metal-rich tropical stream sediment was studied by metagenomics. The metagenome showed complexity of microbial interaction and metabolic processes. Functional analysis highlighted nitrogen and methane metabolic pathways. Metal stress seems to contribute to distinct life strategies in this environment.